Impacto das plataformas digitais na participação popular: um estudo para o desenvolvimento das audiências públicas de Ponta Grossa-PR - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2025)
This research focuses on the development of democracy by exploring the distinct characteristics between the democracy of the ancients and the democracy of the moderns, in connection with the current stage of technological advancement. Understanding not only whether technology can be used to expand popular participation and strengthen democracy, but also whether citizens and their representatives are aligned regarding the possibility of implementing direct democracy, becomes essential. The motivation for this discussion stemmed from the following issue: if the Brazilian government exponentially expanded digital services due to the Covid-19 pandemic, why not use technology to improve the tools for direct public participation in municipal governance? Based on this question, this research project was developed to investigate the feasibility and impacts of implementing a digital platform capable of fostering direct participation in municipal public hearings. In many democratic contexts, public hearings play a fundamental role in promoting civic engagement. However, these events often face challenges related to low attendance, logistical difficulties, and a lack of representativeness. The general objective of this research is to present a study on the feasibility of developing a technological tool aimed at ensuring direct and effective participation in municipal public hearings. To achieve this, the study established specific objectives, including a doctrinal analysis of the evolution of democratic concepts and principles, as well as the forms of public involvement and participation in political matters within a State. It also examined the legal and doctrinal aspects of the popular participation instrument known as the “public hearing.” Finally, a questionnaire was administered to citizens of Ponta Grossa with the purpose of assessing the potential effects of a digital technological tool in promoting civic participation. The aim was to examine their perceptions regarding the effectiveness and appropriateness of the platform, and to gather sufficient information to determine whether it is viable to invest (time and money) in developing a digital platform for conducting municipal public hearings. This study adopted a multidisciplinary approach, combining elements from political science, law, sociology, and information technology. The research employed the “researcher’s diary” method to record key facts that were instrumental in reaching the final conclusion. Based initially on a historical perspective, the study includes a literature review (bibliographic method), analysis of primary data (legislation), as well as a diagnostic evaluation of data collected through a questionnaire administered to local residents (quantitative descriptive research). The original contribution of this research was to provide empirical data sufficient to recognize that the local society lacks a democratic culture, which makes any investment in creating a digital platform or application for conducting public hearings remotely currently unfeasible.
Keywords: Democracia; Participação Popular; Cultura Democrática; Tecnologia; Ciências Sociais Aplicadas